2004
DOI: 10.1124/dmd.104.001230
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of P-Glycoprotein on the Disposition of Drugs Targeted for Indications of the Central Nervous System: Evaluation Using the Mdr1a/1b Knockout Mouse Model

Abstract: ABSTRACT:Thirty-two structurally diverse drugs used for the treatment of various conditions of the central nervous system (CNS), along with two active metabolites, and eight non-CNS drugs were measured in brain, plasma, and cerebrospinal fluid in the P-glycoprotein (P-gp) knockout mouse model after subcutaneous administration, and the data were compared with corresponding data obtained in wild-type mice. Total brain-to-plasma (B/P) ratios for the CNS agents ranged from 0.060 to 24. Of the 34 CNS-active agents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
336
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(368 citation statements)
references
References 25 publications
26
336
2
2
Order By: Relevance
“…For example, studies in Caco-2 cells have given contradicting results for venlafaxine (Ehret et al 2007;Oganesian et al 2009). The antidepressant drug citalopram is another example where different results have been reported in vitro (Rochat et al 1999) and in vivo Doran et al 2005). To study Odm-venlafaxine (desvenlafaxine) and Ndm-venlafaxine separately in our mice model would be of high interest to further elucidate this important issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies in Caco-2 cells have given contradicting results for venlafaxine (Ehret et al 2007;Oganesian et al 2009). The antidepressant drug citalopram is another example where different results have been reported in vitro (Rochat et al 1999) and in vivo Doran et al 2005). To study Odm-venlafaxine (desvenlafaxine) and Ndm-venlafaxine separately in our mice model would be of high interest to further elucidate this important issue.…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacokinetic studies have been published using the abcb1ab knockout mouse model and P-gp has been shown to significantly limit brain entry of a wide variety of drugs including venlafaxine (Doran et al 2005;Kirschbaum et al 2010;Uhr et al 2000;Uhr et al 2008). Using this animal model, we have recently shown that P-gp decreases the brain penetration of the S-and R-enantiomers of venlafaxine and its metabolites after an acute drug challenge (Karlsson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Doran et al [52] very helpfully studied a library of Pfizer's small molecule drugs < 450 Da, measuring both brain and CSF uptake in mice after systemic administration. Reanalysis of their data (Fig.…”
Section: Practical and Clinical Implications Of Isf/csf Interactionmentioning
confidence: 99%
“…However, for such agents, unbound plasma concentrations may need to be greater than values projected using receptor affinity data to achieve adequate receptor occupancy for effect. 57 There have been attempts to establish quantitative structure-activity relationship (QSAR) for P-gp, 58 but the task is made difficult by the broad specificity of this transporter.…”
Section: The Blood-brain Barriermentioning
confidence: 99%